Response to Commentaries: Meta-Analysis of Probability Samples and Other New Evidence. - Blanchard, Ray (Archives of Sexual Behavior, 2018)
The article presents the response to the commentaries about the fraternal birth order effect (FBOE) and maternal immune hypothesis (MIH) on male sexual orientation. It is the author’s view that, the sexual orientation correlates with an individual's number of older brothers increasing the odds of homosexuality. Variety of evidence for the reliability of the FBOE and the effects of such maternal immunization on the future sexual orientation also are discussed.